New PAR1 Agonist Peptide Demonstrates Protective Action in a Mouse Model of Photothrombosis-Induced Brain Ischemia - Galkov, Maksim; Kiseleva, Ekaterina; Gulyaev, Mikhail; Sidorova, Maria; Gorbacheva, Liubov (Frontiers in Neuroscience, 2020)
Protease-activated receptors (PARs) are involved not only in hemostasis but also in the development of ischemic brain injury. In the present work, we examined in vivo effects of a new peptide (AP9) composing Asn47-Phen55 of PAR1 “tethered ligand” generated by activated protein C. We chose a mouse model of photothrombosis (PT)-induced ischemia to assess AP9 effects in vivo. To reveal the molecular mechanism of AP9 action, mice lacking β-arrestin-2 were used. AP9 was injected intravenously once 10 min before PT at doses of 0.2, 2, or 20 mg/kg, or twice, that is, 10 min before and 1 h after PT at a dose of 20 mg/kg. Lesion volume was measured by magnetic resonance imaging and staining of brain sections with tetrazolium salt. Neurologic deficit was estimated using the cylinder and the grid-walk tests. Blood–brain barrier (BBB) disruption was assessed by Evans blue dye extraction. Eosin-hematoxylin staining and immunohistochemical staining were applied to evaluate the number of undamaged neurons and activated glial cells in the penumbra. A single administration of AP9 (20 mg/kg), as well as its two injections (20 mg/kg), decreased brain lesion volume. A double administration of AP9 also reduced BBB disruption and neurological deficit in mice. We did not observe the protective effect of AP9 in mice lacking β-arrestin-2 after PT. Thus, we demonstrated for the first time protective properties of a PAR1 agonist peptide, AP9, in vivo. β-Arrestin-2 was required for the protective action of AP9 in PT-induced brain ischemia.